The Impact of University's Programs Toward Alumni Perceived Development (A Case Study in International Program, Faculty of Economics, Islamic University of Indonesia) - Anas Hidayat; Jaya Addin Linando; Sri Rejeki Ekasasi (INOBIS: Jurnal Inovasi Bisnis dan Manajemen Indonesia, 2018)
Education plays an important role as the value-shaper students. International Program Faculty of Economics, Universitas Islam Indonesia or IPFE UII is one of the universities that have role in education. IPFE UII is intended to be the value-shaper for its students. One of the way that is done by IPFE UII to achieve that goal is by providing several character building programs. IPFE UII compresses the values and tried it into five points, they are: professional behaviour, creative thinking, literacy skill, global understanding and communication skill. This research was done to evaluate whether the programs of IPFE UII have an impact on the perceived development of its students or not. The results of this research shows that based on simple regression analysis, all five variables are significantly influence perceived development as the dependent variable. While the result shown in multiple regression analysis are: 1) professional behaviour has positive significant influence to alumni perceived development; 2) creative thinking has negative influence to alumni perceived development; 3) literacy skill has positive but not significant influence to alumni perceived development; 4) global understanding has positive but not significant influence to alumni perceived development; 5) communication skill has positive influence to alumni perceived development.